2022
DOI: 10.1186/s12889-022-14526-6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels among children, adolescents, adults, and elders in Pakistani population: a cross-sectional study

Abstract: Background Vitamin D is not only an essential part of a healthy diet but it is also known as the sunshine hormone. It helps to absorb calcium and phosphate within the body and is essential for the development of teeth and bones in growing children. Deficiency in vitamin D causes weak bones, osteoporosis in older individuals, and osteomalacia in children. It also causes loss of alveolar bone around the teeth, increased dental cavities, and other problems associated with gum disease. It can cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…A study conducted in china showed highest low levels of vitamin D deficiency in (31.1%) 1-3 years children in comparison to (18.5%) 6-12 years children. 14 This study further highlighted that vitamin D deficiency mostly occurred in winter months (October -March) 51.0% as compared to summer (April -September) 47%. The optimum levels 40ng/ml-100ng/ml of vitamin D were reported in 53% of children in summer while in winter only 39.0% showed optimum levels of vitamin D. The study conducted in Karachi Pakistan on vitamin D status in children in different seasons showed high percentages than this study.…”
Section: Discussionsupporting
confidence: 58%
“…A study conducted in china showed highest low levels of vitamin D deficiency in (31.1%) 1-3 years children in comparison to (18.5%) 6-12 years children. 14 This study further highlighted that vitamin D deficiency mostly occurred in winter months (October -March) 51.0% as compared to summer (April -September) 47%. The optimum levels 40ng/ml-100ng/ml of vitamin D were reported in 53% of children in summer while in winter only 39.0% showed optimum levels of vitamin D. The study conducted in Karachi Pakistan on vitamin D status in children in different seasons showed high percentages than this study.…”
Section: Discussionsupporting
confidence: 58%
“…Phosphate categories: Low < 0.95–1.65 < High. BMI was calculated according to the WHO BMI-for-age boys’, and BMI-for-age girls’ growth charts [ 16 ].…”
Section: Tablementioning
confidence: 99%
“…Thus, the low levels of magnesium results in low serum levels of vitamin D [ 14 ]. In the Middle East, many studies have been carried out to estimate the prevalence of vitamin D deficiency and its risk factors among children and adolescents [ 15 , 16 , 17 ] and only one study conducted among Bahraini children and adolescents [ 3 ]. Therefore, vitamin D status in children and adolescents should be excessively investigated due to the impact of vitamin D on their growth and development as well as prevention of other short- and long-term negative clinical consequences associated with vitamin D deficiency such as rickets, hypertension, cardiovascular diseases, chronic musculoskeletal pain and various cancers [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the United States and Canada, vitamin D deficiency status remains common even with the implementation of fortification strategies (G and Gupta, 2014). The results from other countries, such as Switzerland (Rabufetti et al., 2019), Saudi Arabia (Bushnaq et al., 2022), Armenia (Hutchings et al., 2022), India (Ganie et al., 2022), Russia (Smirnova et al., 2022) and Pakistan (Arshad & Zaidi, 2022), also revealed widespread vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 96%